Pengaruh Bobot Bibit Awal yang Berbeda terhadap Laju Pertumbuhan Rumput Laut Kappaphycus alvarezii dengan Metode Lepas Dasar - Martin Novandi; Henky Irawan; Rika Wulandari (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2022)
There are several factors that will inhibit the growth of seaweed when the cultivation process is the initial stocking density in the off-bottom method. This study aims to determine the effect of different awa seed weights on the growth rate of K. alvarezii seaweed which will provide information regarding the optimal initial weight. This research was carried out in April-May 2021 for 42 days with an acclimatization period of 3 days and preparation of containers for 7 days. Berakit Village, Teluk Sebong District, Bintan Regency, Riau Islands Province. The method used is an experimental method with a completely randomized design (CRD) with 3 treatments with 3 replications. Where the weight of the seeds of treatment A: 50 g, B 100 g, C 150 g, The results of the analysis of the highest absolute growth were obtained in seaweed with initial seed weight of 50 treatments. g with the highest average value of 207.75±9.02b, followed by treatment of 150 g with an average value of 166.78±6.96a and the lowest treatment of 100 g with an average value of 157.04±1.48a. Meanwhile, the highest daily specific growth rate was focused on the 50 g treatment with an average value of 4.95±0.22% b followed by the 150 g treatment with an average value of 3.97±0.17% and the lowest treatment was in the 100 g treatment with an average value of 3.74± 0.04%. Treatment of different initial seedling weight with off-base method gave a significant effect on Absolute Growth (PM) and Daily Specific Growth Rate (LPS) during maintenance.